2010
DOI: 10.1098/rsif.2010.0014.focus
|View full text |Cite
|
Sign up to set email alerts
|

The degradation properties of co-continuous calcium phosphate polyester composites: insights with synchrotron micro-computer tomography

Abstract: This study investigates the in vitro degradation properties of composites consisting of a porous tricalcium phosphate (TCP) foam filled with degradable poly(DL-lactic acid) (PDLLA) via either in situ polymerization or infiltration. The motivation was to develop a material for bone repair that would be initially mechanically strong and would develop porosity during degradation of one of the components. A thorough analysis of the physical in vitro degradation properties has been conducted and reported by the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The in vitro degradation rate of CaP/polymer composites can vary substantially depending on the polymers and the ceramic components, as well as the manufacturing methods 30–32. The CaP/PUR composites in this study degraded slowly in vitro , with the degradation rates in PBS ranging from 0.8 to 2.0 wt %/week.…”
Section: Discussionmentioning
confidence: 84%
“…The in vitro degradation rate of CaP/polymer composites can vary substantially depending on the polymers and the ceramic components, as well as the manufacturing methods 30–32. The CaP/PUR composites in this study degraded slowly in vitro , with the degradation rates in PBS ranging from 0.8 to 2.0 wt %/week.…”
Section: Discussionmentioning
confidence: 84%
“…The complete degradation of pure-phase β-TCP in humans and animal models occurs within a 6–12-month period [ 47 ], which is far quicker than PDLLA (12–30 months) [ 7 , 48 , 49 ] and β-TCP/PDLLA (9–19 months) [ 50 , 51 ]. The rapid resorption will provide more space for tissue ingrowth and release large amounts of Ca 2+ and P 5+ ions into the milieu, which are essential for osteoblast maturation and bone formation [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used manufacturing technology for PDLLA/ β ‐TCP is the in situ copolymerization method. [ 116–118 ] Studies have shown that increasing the amount of β ‐TCP does increase the mechanical properties of the composite scaffolds. In the presence of catalyst, the mechanical properties of the PDLLA/ β ‐TCP composite scaffolds with 30% β ‐TCP added were the best.…”
Section: Bionic “Hard” Scaffolds Of Bioceramics Based On α‐Hydroxy Ca...mentioning
confidence: 99%
“…Compared with the melt penetration method, the bionic bone scaffolds prepared by in situ copolymerization method show better comprehensive performance. [ 118 ] The slightly lower molecular weight of the scaffolds make water absorption and degradation faster. The less force applied to the β ‐TCP surface results in almost no cracks on the surface of the scaffolds and only slight swelling was observed at the ceramic edges.…”
Section: Bionic “Hard” Scaffolds Of Bioceramics Based On α‐Hydroxy Ca...mentioning
confidence: 99%